Economic Crisis, Restrictive Policies, and the Population’s Health and Health Care: The Greek Case - Kondilis, Elias; Giannakopoulos, Stathis; Gavana, Magda; Ierodiakonou, Ioanna; Waitzkin, Howard; Benos, Alexis (American journal of public health (1971), 2013)
The global economic crisis has affected the Greek economy with unprecedented severity, making Greece an important test of the relationship between socioeconomic determinants and a population’s well-being. Suicide and homicide mortality rates among men increased by 22.7% and 27.6%, respectively, between 2007 and 2009, and mental disorders, substance abuse, and infectious disease morbidity showed deteriorating trends during 2010 and 2011. Utilization of public inpatient and primary care services rose by 6.2% and 21.9%, respectively, between 2010 and 2011, while the Ministry of Health’s total expenditures fell by 23.7% between 2009 and 2011. In a time of economic turmoil, rising health care needs and increasing demand for public services collide with austerity and privatization policies, exposing Greece’s population health to further risks.